A Subsidy Strategy to Boost the Activity of Small Milk Producers in Morocco - Ali Labriji; Youssef El Foutayeni; Mostafa Rachik (Journal of Applied Mathematics)
The dairy sector in Morocco is a sector that struggles to develop by facing several difficulties. Therefore, a significant gap has emerged between the main national producers and small farmers, while in the economy, the development of small economic actors presents an important lever of growth. If we assume that the consumer’s milk demand function is linear, that it depends only on the consumer’s price, and that production costs follow a decreasing return, and finally, by considering only two actors representing the different types of producers, we will show in this paper that a competitive production subsidy of 0.5 MAD can triple the market share of small farmers while being in a situation of Nash-Cournot’s equilibrium. In addition, the addition of a subsidy to production costs will reduce the price of milk and, thus, increase the annual milk consumption of Moroccans from 59 liters, which is below the world average consumption, to 94 liters annually, thus benefiting the consumer in addition to small farmers.